Kampanye Kreatif Iklan “Bleh Sabbath” pada Brand Pakaian - Wanda Vernando; Indri Rachmawati (UNISBA Press, 2022)
Abstract. In the 21st century, especially business actors are required to be able to keep up with the times, innovative, and creative. Goods and services products continue to emerge, the competition of business people who want to win the market by using advertising is getting tighter, it certainly becomes its own demands for business actors to be able to present a creative campaign in order to attract the interest of the audience. Nasi Padang Everyday is a clothing brand that was originally a movement developed as a form of movement for padang rice lovers. Current business competition makes Nasi Padang Everyday must be able to compete with other business people who are also more aggressive in advertising, therefore the right advertising creative strategy is needed in order to win the hearts of the audience. In this study, the author focused on discussing the creative advertising campaign